Development of software for prediction and virtual screening of antioxidant activity of new synthesized azaheterocyclic compounds - Ryzhenko, Victor P.; Belenichev, Igor F.; Samura, Iryna B.; Ryzhov, Oleksii A. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Increasing introduction of innovation technologies into medicine and pharmacology makes it possible to modify and develop further the methods of the development of new medicines. Such methods include virtual screening. In this article approaches to building software for virtual screening of nitric oxide (NO)scavengers in an important class of azaheterocyclic compounds are discussed. Methods: During the study period (from October 2017 to January 2019) the methods for the evaluation of antioxidant activity, as well as quantum-mechanical and statistical calculations were conducted. Quantum-mechanical calculations on HOMO (highest occupied molecular orbital) energy and LUMO (lowest unoccupied molecular orbital) energy descriptors have been conducted using program complex WinMopac 7.2. Results: Evaluation methods of antioxidant activity, quantum-mechanical and statistical calculations have been presented. The algorithm for computer program of virtual screening has been proposed. Prospects and benefits of computer modeling of agent activity are considered. Conclusions: Establishment of computer program for virtual screening will significantly reduce time and resources during researching new synthesized compounds. The algorithm for a computer program of virtual screening has been developed Predictable antioxidant activity data on nitric oxide radical (NO·)inhibition may be calculated in percentage using HOMO and LUMO as the input data for this program.